Estudo da estabilização granulométrica e química de material fresado com adição de cimento Portland e cinza de casca de arroz para aplicação em camadas de pavimentos - Pires, Gustavo Menegusso (2014)
Road transport is of great importance for many countries, in Brazil it can be even more extreme, due to the concentration of cargo through this modal. We also know that maintenance costs are elevated, forcing managers and researchers to find new alternatives to increase the utilization of materials, reduce energy consumption, speed up restoration interventions, among others. Besides the high costs, another important factor that stands out is the environmental issue, which is directly affected in the construction and maintenance of highways, whether using natural materials, movements of soils, in the fuel used by the equipment, etc. Thus, it becomes feasible to study reuse of old materials in the execution of highways recycling of deteriorated pavement, because all the material can be used for construction of a new layer, and with little addition of new materials for stabilization, reducing the consumption. Therefore, the material deteriorated asphalt pavement, the Reclaimed Asphalt Pavement (RAP), is the objective of this research, aiming to stabilize pavement layers in two ways, the particle size and chemical stabilization, the latter with the addition of Portland cement and rice husk ash. This research aims to evaluate, through laboratory testing, the feasibility of using pure and stabilized milled material (mechanical, chemical and particle size) in layers of flexible pavements. The milled materials are from BR-290 and ERS-509. Particle size stabilization was performed and determined the level of 70% of milled material and 30% of natural aggregate. For testing of compressive strength were molded into test specimens of 10x20 cm with different levels of Portland cement (CP IV-32), and determine the content of 4,86% (BR-290) and 5,37% (ERS-569) from the compressive strength of 2.1 MPa at 28 days. From the results obtained, specimens were molded for testing the Axial compressive strength, tensile strength by diametrical compression and resilient modulus; in these specimens, the cement was replaced by Rice Husk Ash (mesh #325 and #500) in ratios of 15, 30 and 50% by weight of cement content, and put into moist chamber for 7, 28 and 160 curing days. The results showed that the amount of 15% of CCA reached values very close to the reference mixtures. The satisfactory performance confirms the possibility to cover studies of these materials.